Experimental Study of the Aggregate Shapes in Self-Compaction - Mehrdad Mohaddes Pour; Seyed Sina Razavi Taheri (Shock and Vibration)
Compaction operations have a vital role in embankments or rock fills to avoid settlement, but in some projects, such as marine ones, it is hardly possible to accomplish compaction operations due to the problems and executive limitations. In situations with no possibility of compaction, it is recommended to use single-size or self-compacted materials. From a theoretical point of view, self-compacted materials consist of coarse aggregates with no vast domain of gradation. In this case, the porosity of the materials in the dense state is not significantly different from the loose one, and a relatively dense condition occurs after it is poured; thus, the mass of materials will undergo lower volumetric changes in the future. In this study, the self-compacted characteristic of materials has been investigated using real aggregates with different gradations (the ratio of the largest to the smallest aggregate size of 1, 2, 4, and 8). The gradation and shape of aggregates are the main variables examined in the research. Real aggregates have been used in order to compare the study of self-compacted idea with ideal aggregates and the effects of sphericity and angularity of them. According to the experiments carried out on samples in the present work, it was observed that, without compaction operations, even ideal materials would not be in fully self-compacted state. However, relatively denser conditions can be achieved by observing the necessary points. Moreover, aggregates with high sphericity have better self-compacted property. Furthermore, the more uniform gradation and bigger size of materials lead to more self-compacted pile of materials.